Cellulose Fundamentals and Conversion Into Biofuel and Useful Chemicals - Banu Jeyakumar, Rajesh; Sankarapandian, Kavitha; Kannah Ravi, Yukesh (IntechOpen, 2023)
This book presents a comprehensive overview of the advanced method of converting cellulose into biofuels and value-added products. It presents detailed information about the application of cellulose in the food and packing industry. In addition, it discusses lignocellulosic-based cellulose and its uses and the application of cellulose in water desalination and wastewater treatment. This book is useful for environmental/chemical engineers, technicians, and academic researchers to gather knowledge on various applications of cellulose and the possible way of converting cellulose into biofuels and other value-added products.